Social integration after moving to a new city predicts lower systolic blood pressure. (22nd August 2021) - Roddick, Charlotte M.; Christie, Chelsea D.; Madden, Kenneth M.; Chen, Frances S.
Abstract: Residential mobility is linked to higher incidence of cardiovascular disease (CVD) and mortality. A mechanism by which residential relocation may impact health is through the disruption of social networks. To examine whether moving to a new city is associated with increased CVD risk and whether the extent to which movers rebuild their social network after relocating predicts improved CVD risk and psychosocial well‐being, recent movers ( n  = 26), and age‐ and sex‐matched nonmovers ( n  = 20) were followed over 3 months. Blood pressure, C‐reactive protein/albumin ratio (CRP/ALB), social network size, and psychosocial well‐being were measured at intake (within 6 weeks of residential relocation for movers) and 3 months later. Multiple regression indicated higher systolic blood pressure (SBP) for movers ( M  = 107.42, SD  = 11.39), compared with nonmovers ( M  = 102.37, SD  = 10.03) at intake, though this trend was not statistically significant. As predicted, increases in movers' social network size over 3 months predicted decreases in SBP, even after controlling for age, sex, and waist‐to‐hip ratio, b  = −2.04 mmHg, 95% CI [−3.35, −.73]. Associations between increases in movers' social ties and decreases in depressive symptoms and stress were in the predicted direction but did not meet the traditional cutoff for statistical significance. Residential relocation and movers' social network size were not associated with CRP/ALB in this healthy sample. This study provides preliminary evidence for increased SBP among recent movers; furthermore, it suggests that this elevation in CVD risk may decrease as individuals successfully rebuild their social network. Abstract : This study examines the psychophysiological effects of social integration following a residential move. We demonstrate that making more new social connections predicts decreased systolic blood pressure and improved psychosocial wellbeing among recent movers. These prospective findings complement existing research on the benefits of social connection by directly examining the cardiovascular physiology of movers as they transition into a new community.